The impact of migration on wages in Costa Rica - Adriana R. Cardozo Silva; Luis R. Díaz Pavez; Inmaculada Martínez-Zarzoso (Migration Studies, 2023)
In recent years, Costa Rica has experienced greater international migration from neighboring countries due to political, economic, and social reasons, raising discussions on the impact of migration on wages of native Costa Rican workers. This article is the first that disentangles the impact of migration on wages for native Costa Ricans from the impact for settled immigrants by analyzing the effect within groups of education, experience, and regions and controlling for unobserved heterogeneity. We find that on average, there is a significant negative effect of recent immigration on the wages of established immigrants, but no significant effect on the wages of natives over the period from 2012 to 2019. The outcomes hold when using different units of analysis and identification strategies.
Keywords: 330; Immigration; wages; labor markets; Costa Rica